1969
DOI: 10.1093/jee/62.4.772
|View full text |Cite
|
Sign up to set email alerts
|

Common Leafhopper-Planthopper Populations and Incidence of Tungro Virus in Diazinon-Treated and Untreated Rice Plots1

Abstract: Field experiments during 2 consecutive rice crops showed the relative abundance of common rice leafhopper and planthopper species as Nephotettix spp. > Sogatella furcifera (Horvath) > Nilaparvata lugens (Stil) > lnawl11a dorsalis (Motschulsky). The Nephotettix spp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Alam [11] found that crop age has a highly significant effect on populations. In addition, BPH tends to be more numerous after 60 days' post-transplantation when crops are close to maturity, as well as between the heading and harvesting stages during dry seasons [12,13]. Otuka et al [14] found that BPH is a monophagous insect whose occurrence depends on host rice plants.…”
Section: Introductionmentioning
confidence: 99%
“…Alam [11] found that crop age has a highly significant effect on populations. In addition, BPH tends to be more numerous after 60 days' post-transplantation when crops are close to maturity, as well as between the heading and harvesting stages during dry seasons [12,13]. Otuka et al [14] found that BPH is a monophagous insect whose occurrence depends on host rice plants.…”
Section: Introductionmentioning
confidence: 99%
“…The other insecticides which have been reported to be effective against the tungro vector are phorate (Pathak ef a/., 1967), diazinon (Bae and Pathak, 1969), carbofuran (Rao and Anjaneyulu, 1979;Shukla and Anjaneyulu, 1980;Satapathy and Anjaneyulu, 1986), and FMC 35001, phosphomidon, oxydemeton-methyl and bendiocarb (Satapathy and Anjaneyulu, 1983).…”
Section: Field Evaluationmentioning
confidence: 99%